The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.21513/2410-8758-2017-2-130-143
|View full text |Cite
|
Sign up to set email alerts
|

Dangerous Atmospheric Drought in European Russia Under Recent Summer Warming

Abstract: Резюме. В статье исследованы тенденции экстремального агроме-теорологического явления -опасной атмосферной засухи (ОАЗ) -и региональные особенности условий ее формирования на Европейской части России (ЕЧР) во второй половине XX -начале XXI века. В ЕЧР южнее 57 ° с.ш. за период более теплой Северной Атлантики (1995 -2014 года) по сравнению с ее более холодным периодом (1963 -1994 года) выявлено увеличение повторяемости периодов аномально высо-ких температур длительностью больше месяца. При этом в мае на больш… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Several studies (e.g., References [47,49,55,58,78]) demonstrated that the EE/WR region has been associated with an increase in the occurrence of more meridional ECM or NH flow regimes, especially during the summer (Figure 5D). The study region has also been associated with an increase in atmospheric blocking (e.g., References [44][45][46][47]55,57,58]) and studies of drought associated with the extreme summer-season drought of 2010 over this region associated extreme dry summers with atmospheric blocking.…”
Section: Dry Summer Seasonsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies (e.g., References [47,49,55,58,78]) demonstrated that the EE/WR region has been associated with an increase in the occurrence of more meridional ECM or NH flow regimes, especially during the summer (Figure 5D). The study region has also been associated with an increase in atmospheric blocking (e.g., References [44][45][46][47]55,57,58]) and studies of drought associated with the extreme summer-season drought of 2010 over this region associated extreme dry summers with atmospheric blocking.…”
Section: Dry Summer Seasonsmentioning
confidence: 99%
“…They linked the transition of ENSO with dry summers. Then Reference [47] (which Reference [44] supports) linked a warmer drier climate of Southwestern Russia with the increase in certain weather types, including blocking.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…ridge is related to the rise in the frequency and intensity of blocking anticyclones in the Atlantic-European region (Cherenkova 2017). The decrease in extreme summer temperatures in the southeast Ural is also due to the same process, since arctic air masses spread to the Western Siberia along the eastern periphery of these blockings.…”
Section: Table 1 Average Maximum and Minimum Values Of The Differenmentioning
confidence: 94%